ANALISIS KADAR α-TOKOFEROL (VITAMIN E) DALAM DAUN KELOR (Moringa oleifera Lam) DARI DAERAH PESISIR DAN PEGUNUNGAN SERTA POTENSINYA SEBAGAI ANTIOKSIDAN - Khalil Mubarak; Hasnah Natsir; Abd. Wahid Wahab; Pasjan Satrimafitrah (KOVALEN: Jurnal Riset Kimia, 2017)
Alpha-tocopherol, a major vitamin E component, functions as an antioxidant that neutralizes free radicals in a living organism. Moringa oleifera Lam. leaves are rich source of carotenoids and -tocopherol. This research was aimed to determine the concentration of α-tocopherol and examine the activity of moringa leaves (Moringa  oleifera L.) crude extracts as an antioxidant. Sample used in this research were juvenile and adult moringa leaves (Moringa oleifera L), which were taken from seashore of Barru regency and highland of Soppeng regency. Extraction of the leaves was carried out by reflux method using ethanol as a solvent, and then evaporated to produce concentrated ethanol extract. Analyzes were detected at wavelenght of 510.20 nm using UV-Vis Spectroscopy, the results indicated that concentration of α-tocopherol extracted from juvenile and adult moringa leaves from seashore area were 104.52 mg/100g and 11.419 mg/100g respectively, whilst the leaves from highland area gave a concentration of 134.4 mg/100g and 114.918 mg/100g. Next, we examined the antioxidant activity of each type of leaf using DPPH (1,1-diphenyl-2-picrylhydrazyl) methods at the wavelength of 515 nm. The IC50 results data showed that ethanol extract of juvenile and adult leaves from seashore area were 172.71 μg/mL and 258.92 μg/mL respectively, and categorized as weak antioxidant. Adversely, juvenile leaves from highland area gave a result of 97.79 μg/mL and categorized as strong antioxidant; while adult leaves from the same area gave a values of 143.14 μL/mL and categorized as medium antioxidant. Vitamin E and BHT were used as control and had higher values compared to all samples.Keywords: α-tocopherol, antioxidant, Moringa oleifera leaves, DPPH, UV-Vis Spectrophotometer.